DIAGRAM ALIRAN DATA DAN KONSEP BASIS DATA SISTEM INFORMASI MANAJEMEN PETERNAKAN BROILER - Ahmad Sanmorino; Isabella Isabella (Jurnal Informatika Global)
This article contains results of design management information system broiler farms that have been done by researchers. The design of management information system is done based on the data flow and entity contained in the broiler farm that serves as the object of research. The design of management information system begins with the concept of database and data flow diagram. Database concept is used to know the database structure used by broiler farm management information system as a whole. While the data flow diagram used to describe all the processes involved in broiler farm management. The results of the design conducted by researchers can be used for the development stage of broiler farm management information system.    Key words : Database, Data flow diagram, Management information system, Broiler farm.